Research progress of sol-gel ceramic coating : A review - Aliaa, Zanurin; Nor Azmi, Hj Johari; Juliawati, Alias; Mas Ayu, Hassan; Norizah, Hj Redzuan; Sudin, Izman (Elsevier Ltd, 2021)
The sol-gel method is a simple and low-cost technique that requires low temperature for the reaction process. Sol-gels can be made from a wide variety of ceramic materials, including alumina, chromium, silica, and zirconium. This technique has been used in a variety of applications, including corrosion prevention, biomedical applications, and electronic devices. The sol-gel technique has made significant progress in a variety of fabrication applications. Numerous papers have reported on the incorporation of ceramic materials with other materials to increase the performance of sol-gel coating. The ceramic sol-gel coating increased the corrosion resistance and thermal properties of the coated materials while remaining a low-cost approach. This paper highlights current reports on the various applications of sol-gel ceramic coatings.